Citizen e-Participation as an Important Factor for Sustainable Development - Musiał-Karg, Magdalena; Kapsa, Izabela (European Journal of Sustainable Development, 2019)
Citizen e-participation – in times of rapid ICT advancement – is an important factor contributing to the development of contemporary democracies. The use of electronic citizen involvement tools provides numerous changes in the relationship between the citizen and public institution, especially by boosting citizen engagement in decision making. Civic participation is a key factor in determining effective and inclusive governance at the local and national levels. As many organizations have recognized, contemporary democracy needs to ensure a responsive, inclusive, participatory and representative decision-making process, emphasizing the importance of those sustainable development factors. Moreover, National Councils for Sustainable Development were once considered critical to achieving integration in decision-making and participation, two dimensions that were at the heart of the sustainable development concept. The article presents citizen e-participation as an important factor for sustainable development. The purpose is to explain theoretical and empirical meaning of citizen e-participation for sustainable development. To achieve this goal, the authors used the following research methods: critical review of the literature and quantitative data analysis (data examined come from author’s own research (2018) into use and willingness to use e-government tools by Poles). Research findings may be an important contribution to the development of civic participation and the implicit value of the process. Keywords: citizen participation, e-democracy, e-government, e-participation, Poland, sustainable development.